ANALYSIS OF FACTORS AFFECTING THE TIMING OF PATIENTS SEEKING MEDICAL CARE IN ACUTE CORONARY SYNDROME WITH ST-SEGMENT ELEVATION - Юлия Александровна Солопова; Михаил Юрьевич Огарков; Артем Юрьевич Янкин; Юрий Григорьевич Гущин; Марина Александровна Шулакова; Евгений Николаевич Марешин; Надежда Михайловна Шахшнейдер; Ольга Анатольевна Горелкина (Медицина в Кузбассе, 2019)
Subject of research. Time «pain-call ambulance».